Core-sheath composite fiber, its manufacturing method, and fiber structure
Patent Information
- Application Number
- JP2023503834
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-04
- Filing Date
- 2022-02-28
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-02-28
AI Technical Summary
【0017】 本発明の芯鞘複合繊維によれば、芯成分として溶融異方性芳香族ポリエステルを有し、鞘成分が海島構造である芯鞘複合繊維において、鞘成分の島部を溶融異方性芳香族ポリエステルとしてその割合を高めた場合であっても、島部を微分散させることにより紡糸中の島成分の凝集が抑制され、芯鞘複合繊維の耐フィブリル性を向上することができ、耐摩耗性に優れた繊維が得られる。
Smart Images

Figure 0007645984000009 
Figure 0007645984000010 
Figure 0007645984000011
Abstract
Description
Related Applications
[0001] This application claims priority to Patent Application No. 2021-34707, filed in Japan on March 4, 2021, the entire contents of which are incorporated by reference into this application. [Technical field]
[0002] The present invention relates to a core-sheath composite fiber having a melt-anisotropic aromatic polyester as a core component, which has improved fibrillation resistance and excellent abrasion resistance, a production method thereof, and a fiber structure. [Background technology]
[0003] It is known that melt-dispersed aromatic polyester fibers have high tenacity and high elastic modulus, but these fibers have a problem that they easily fibrillate due to wear because the molecular chains are highly oriented in the fiber axis direction. Therefore, a composite fiber has been proposed that uses a melt-dispersed aromatic polyester as a core component while suppressing fibrillation by covering the periphery with a sheath component.
[0004] For example, Patent Document 1 (JP 2002-20932 A) discloses a conjugated fiber having a core component made of a melt-anisotropic aromatic polyester (A) and a sheath component made of a flexible polyester (B) containing 0 to 10% of the polymer (A), the intrinsic viscosity [η] of the polyester (B) being 0.65 dl / g or more.
[0005] Patent Document 1 describes that blending the sheath component with the same polymer as the core component increases the strength of the sheath component and at the same time increases the adhesiveness with the core component.
[0006] Patent Document 2 (JP 2008-255535 A) discloses a core-sheath composite fiber that satisfies the following: a core component is made of a melt-type anisotropic aromatic polyester (A polymer), a sheath component has a sea-island structure with a sheath component ratio of 0.2 to 0.7, a sea component constituting the sheath component is made of a flexible thermoplastic polymer (B polymer), and an island component is made of a melt-type anisotropic aromatic polyester (C polymer), and the island component ratio in the sheath component is 0 to 0.25, and that has 0.03 to 2.5 mass % of inorganic fine particles mainly composed of a silicate compound attached to the fiber surface.
[0007] Patent document 2 describes that since a polymer without melt anisotropy has low adhesion to a melt anisotropic polyester and is easily peeled off, the sheath component is formed from a blend of a melt anisotropic polyester and a polymer without melt anisotropy. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2002-20932 A [Patent Document 2] JP 2008-255535 A Summary of the Invention [Problem to be solved by the invention]
[0009] However, Patent Document 1 denies increasing the proportion of the melt-type anisotropic aromatic polyester in the sheath component, because if the proportion of the melt-type anisotropic aromatic polyester in the sheath component exceeds 10%, unevenness will occur on the fiber surface and spinnability will deteriorate.
[0010] In addition, Patent Document 2 describes that the composite fiber described in Patent Document 2 can suppress adhesion between fibers and improve reeling properties by attaching 0.03 to 2.5 mass % of inorganic microparticles mainly composed of a silicate compound to the fiber surface, but only mentions that, regarding the suppression of fiber fibrillation, the use of a flexible thermoplastic polymer as the sea component significantly improves fibrillation resistance and abrasion resistance.
[0011] If it were possible to incorporate a large amount of melt-type anisotropic aromatic polyester into the sheath component of a core-sheath composite fiber, in which the core component is a melt-type anisotropic aromatic polyester and the periphery is covered with a sheath component, without impairing spinnability, it would be possible to strengthen the adhesion between the core and the sheath, suppress sheath peeling, and realize higher abrasion resistance than ever before. For the same reason, it would also be possible to make the sheath thinner, which would result in increased strength due to the melt-type anisotropic aromatic polyester on the core side, which is preferable.
[0012] Therefore, an object of the present invention is to provide a core-sheath composite fiber having excellent abrasion resistance, which increases the proportion of melt-anisotropic aromatic polyester in the sheath component of the core-sheath composite fiber while suppressing fibrillation and deterioration of spinnability. [Means for solving the problem]
[0013] As a result of intensive research into achieving the above-mentioned object, the inventors of the present invention have found that in a core-sheath composite fiber having a melt-anisotropic aromatic polyester as a core component, (I) when the sheath component has a sea-island structure having islands made of melt-anisotropic aromatic polyester and the proportion of the melt-anisotropic aromatic polyester in the sea-island structure is increased, peeling of the sheath is prevented by improving the adhesion between the core and sheath, and abrasion resistance is further improved while the sheath can be made thinner, and strength can be increased due to the melt-anisotropic aromatic polyester of the core component. However, (II) on the other hand, spinning condition is significantly deteriorated due to the high proportion of the melt-anisotropic aromatic polyester, and the sheath component is fibrillated. Thus, they have found it to be a new objective to improve the spinning condition and suppress the fibrillation of the sheath component. Then, (III) it was discovered that by increasing the proportion of molten anisotropic aromatic polyester in the sheath component, kneading the sheath component at a specific temperature, and drawing up the discharged yarn at a specific draft value, it is possible to finely disperse island portions made of molten anisotropic aromatic polyester in the sea portion and control the shape of the island portions, and as a result, even when the proportion of molten anisotropic aromatic polyester in the sheath component is high, it is possible to suppress fibrillation of the core-sheath composite fiber while maintaining good spinning condition, and to improve abrasion resistance even when the sheath is made thin, thereby completing the present invention.
[0014] That is, the present invention can be configured in the following manner. [Aspect 1] A core-sheath composite fiber having a sea-island structure in which a core component contains a melt-type anisotropic aromatic polyester (A polymer), a sheath component contains a flexible thermoplastic polymer (B polymer) and a melt-type anisotropic aromatic polyester (C polymer), the B polymer forms a sea component, the C polymer forms island components, and a plurality of island components made of the island components are dispersed in a sea part made of the sea component, The ratio of the island components in the sheath component is more than 10% by weight, and In a cross section of the sheath-core composite fiber cut in the longitudinal direction of the fiber, the maximum width W of an island portion having the largest width in a direction perpendicular to the fiber is 0.65 μm or less (preferably 0.60 μm or less, more preferably 0.55 μm or less, and even more preferably 0.50 μm or less), a sheath-core composite fiber, wherein in an island portion having the maximum width W, among the island portions that are in contact with an oblique line in the sheath component extending at a predetermined angle of 10° with respect to the longitudinal direction of the fiber from one end to the other end in the longitudinal direction of the fiber, the ratio L1 / W of the maximum length L1 of the oblique length that overlaps with the oblique line to the maximum width W of the island portion is 5.0 or more (preferably 5.1 or more, more preferably 5.2 or more, even more preferably 5.3 or more, and even more preferably 5.5 or more). [Aspect 2] A sheath-core composite fiber according to aspect 1, wherein the maximum length L1 of the oblique length is 1.0 μm or more (preferably 1.3 μm or more, more preferably 1.5 μm or more, and even more preferably 1.7 μm or more). [Aspect 3] A sheath-core composite fiber according to aspect 1 or 2, wherein in a cross section of the sheath-core composite fiber cut in the longitudinal direction of the fiber, the length L2 of the island portion in the sheath component in the longitudinal direction of the fiber is 450 to 1000 μm (preferably 500 to 800 μm, and more preferably 550 to 650 μm). Aspect 4 The sheath / core composite fiber according to any one of aspects 1 to 3, wherein the thickness of the sheath component is 0.8 to 5.0 μm (preferably 0.9 to 4.0 μm, more preferably 0.9 to 3.8 μm). Aspect 5 A sheath-core conjugate fiber according to any one of aspects 1 to 4, wherein the A polymer and the C polymer are the same type of melt-anisotropic aromatic polyester. Aspect 6 A core-sheath composite fiber according to any one of aspects 1 to 5, wherein the weight ratio of the core component to the sheath component, that is, core component / sheath component, is 20 / 80 to 97 / 3 (preferably 50 / 50 to 96 / 4, more preferably 60 / 40 to 95 / 5, even more preferably 70 / 30 to 94 / 6, still more preferably 75 / 25 to 93 / 7, particularly preferably 80 / 20 to 92 / 8, and most preferably 82.5 / 17.5 to 90 / 10). Aspect 7 A sheath-core conjugate fiber according to any one of aspects 1 to 6, wherein the single fiber fineness of the sheath-core conjugate fiber is 1 to 120 dtex (preferably 2 to 60 dtex, more preferably 2.5 to 30 dtex, and even more preferably 3 to 15 dtex). Aspect 8 A method for producing a core-sheath composite fiber having a sea-island structure in which a core component contains a melt-type anisotropic aromatic polyester (A polymer), a sheath component contains a flexible thermoplastic polymer (B polymer) and a melt-type anisotropic aromatic polyester (C polymer), the B polymer forms a sea component, the C polymer forms island components, and a plurality of island components made of the island components are dispersed in a sea part made of the sea component, the method comprising the steps of: a kneading step in which the B polymer and the C polymer used for the sheath component are kneaded using a twin-screw extruder at a temperature of (Mb)°C or higher relative to the melting point (Mb) of the B polymer and at a temperature of (Mc-20)°C or higher but lower than (Mc)°C relative to the melting point (Mc)°C of the C polymer, and the A polymer used for the core component is melted and kneaded using an extruder different from the twin-screw extruder used for the sheath component; and a discharge step in which the sheath component and the core component respectively kneaded in this kneading step are combined and discharged to obtain a discharged yarn. A step of taking up the discharged discharged yarn at a draft value, which is the ratio of the winding speed to the discharge speed, of 13 to 50 (preferably 15 to 45, more preferably 16 to 40, even more preferably 19 to 38, and particularly preferably 20 to 35); A method for producing a core-sheath composite fiber comprising at least the steps of: Aspect 9 A method for producing a sheath-core composite fiber according to aspect 8, comprising a heat treatment step of subjecting the fiber obtained in the discharge step to a heat treatment. Aspect 11 A fiber structure comprising at least a part of the core-sheath composite fiber according to any one of the first to seventh embodiments.
[0015] In this specification, the term "cross section of a sheath-core composite fiber cut in the fiber longitudinal direction" is synonymous with the cross section of a sheath-core composite fiber cut in a plane including the fiber longitudinal direction, and may be referred to as the "fiber longitudinal section" hereinafter. The fiber perpendicular direction means the direction perpendicular to the fiber longitudinal direction (or the direction perpendicular to the fiber longitudinal direction) in the fiber longitudinal section.
[0016] It should be noted that any combination of at least two elements disclosed in the claims and / or the specification and / or the drawings is included in the present invention. In particular, any combination of two or more of the claims described in the claims is included in the present invention. Effect of the Invention
[0017] According to the sheath-core composite fiber of the present invention, in a core-sheath composite fiber having a melt-anisotropic aromatic polyester as a core component and a sheath component having an island-sea structure, even when the island parts of the sheath component are made of a melt-anisotropic aromatic polyester to increase the proportion thereof, aggregation of the island parts during spinning can be suppressed by finely dispersing the island parts, and the fibrillation resistance of the core-sheath composite fiber can be improved, thereby providing a fiber with excellent abrasion resistance. [Brief description of the drawings]
[0018] The present invention will be more clearly understood from the following description of preferred embodiments with reference to the accompanying drawings. However, the embodiments and drawings are merely for illustration and explanation, and should not be used to define the scope of the present invention. The scope of the present invention is defined by the appended claims. In the accompanying drawings, the same part numbers in multiple drawings indicate the same parts. [Figure 1A] FIG. 1 is a schematic perspective view of a core-sheath composite fiber according to one embodiment of the present invention. [Figure 1B] FIG. 2 is a schematic cross-sectional view of a concentric sheath composite fiber cut in the fiber longitudinal direction. [Diagram 2] FIG. 2 is an enlarged schematic cross-sectional view showing a part of a sheath component of a concentric sheath composite fiber. [Diagram 3]FIG. 2 is a schematic cross-sectional view of a concentric sheath composite fiber cut along a plane perpendicular to the longitudinal direction of the fiber. [Figure 4] FIG. 1 is a schematic cross-sectional view showing the structure of a spinneret used in spinning concentric sheath composite fibers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The present invention will be described in detail below with reference to examples. One aspect of the present invention is a core-sheath composite fiber having a core component and a sheath component covering the core component, and the sheath component has a sea-island structure containing a sea component and island components. The core component contains a molten anisotropic aromatic polyester (A polymer), and the sheath component contains a flexible thermoplastic polymer (B polymer) and a molten anisotropic aromatic polyester (C polymer), with the B polymer forming the sea component and the C polymer forming the island components.
[0020] (core component) The melt anisotropic aromatic polyester (A polymer) used for the core component is a polymer that exhibits optical anisotropy (liquid crystallinity) in the molten phase. For example, a sample is placed on a hot stage, heated under a nitrogen atmosphere, and the transmitted light of the sample is observed to determine whether it is a melt anisotropic aromatic polyester. The melt anisotropic aromatic polyester of the present invention is composed of repeating structural units derived from, for example, aromatic diols, aromatic dicarboxylic acids, aromatic hydroxycarboxylic acids, etc., and the structural units derived from aromatic diols, aromatic dicarboxylic acids, and aromatic hydroxycarboxylic acids are not particularly limited in terms of their chemical structure, so long as they do not impair the effects of the present invention. In addition, the melt anisotropic aromatic polyester may contain structural units derived from aromatic diamines, aromatic hydroxyamines, or aromatic aminocarboxylic acids, so long as they do not impair the effects of the present invention. For example, examples of preferred structural units are shown in Table 1.
[0021] [Table 1]
[0022] In the structural units in Table 1, m is an integer of 0 to 2, and Y in the formula, in the range of 1 to the maximum number that can be substituted, each independently represents a hydrogen atom, a halogen atom (e.g., a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, etc.), an alkyl group (e.g., an alkyl group having 1 to 4 carbon atoms such as a methyl group, an ethyl group, an isopropyl group, a t-butyl group, etc.), an alkoxy group (e.g., a methoxy group, an ethoxy group, an isopropoxy group, a n-butoxy group, etc.), an aryl group (e.g., a phenyl group, a naphthyl group, etc.), an aralkyl group [benzyl group (phenylmethyl group), phenethyl group (phenylethyl group), etc.], an aryloxy group (e.g., a phenoxy group), an aralkyloxy group (e.g., a benzyloxy group), etc.).
[0023] More preferred structural units include the structural units described in Examples (1) to (18) in Tables 2, 3, and 4. When a structural unit in the formula is a structural unit that can exhibit multiple structures, two or more of such structural units may be combined and used as a structural unit that constitutes a polymer.
[0024] [Table 2]
[0025] [Table 3]
[0026] [Table 4]
[0027] In the structural units of Tables 2, 3 and 4, n is an integer of 1 or 2, and each structural unit n=1, n=2 may exist alone or in combination, and Y1 and Y2 may each independently be a hydrogen atom, a halogen atom (e.g., a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, etc.), an alkyl group (e.g., an alkyl group having 1 to 4 carbon atoms such as a methyl group, an ethyl group, an isopropyl group, a t-butyl group, etc.), an alkoxy group (e.g., a methoxy group, an ethoxy group, an isopropoxy group, an n-butoxy group, etc.), an aryl group (e.g., a phenyl group, a naphthyl group, etc.), an aralkyl group [benzyl group (phenylmethyl group), phenethyl group (phenylethyl group), etc.], an aryloxy group (e.g., a phenoxy group, etc.), an aralkyloxy group (e.g., a benzyloxy group, etc.), etc. Among these, a hydrogen atom, a chlorine atom, a bromine atom, or a methyl group is preferred.
[0028] Furthermore, examples of Z include substituents represented by the following formulas.
[0029] [ka]
[0030] The melt-anisotropic aromatic polyester may preferably be a combination having a naphthalene skeleton as a structural unit. It is particularly preferable to include both a structural unit (A) derived from hydroxybenzoic acid (abbreviation: HBA) and a structural unit (B) derived from hydroxynaphthoic acid (abbreviation: HNA). For example, the structural unit (A) may be the following formula (A), and the structural unit (B) may be the following formula (B). From the viewpoint of improving melt moldability, the ratio of the structural unit (A) to the structural unit (B) may be preferably in the range of 9 / 1 to 1 / 1, more preferably 7 / 1 to 1 / 1, and even more preferably 5 / 1 to 1 / 1.
[0031] [ka]
[0032] [ka]
[0033] The total of the constituent units (A) and the constituent units (B) may be, for example, 65 mol % or more, more preferably 70 mol % or more, and even more preferably 80 mol % or more, based on the total constituent units. In particular, a melt-type anisotropic aromatic polyester in which the constituent units (B) account for 4 to 45 mol % of the polymer is preferred.
[0034] The melting point of the melt anisotropic aromatic polyester preferably used in the present invention is preferably in the range of 250 to 360° C., more preferably 260 to 320° C. The melting point referred to here is measured by a test method in accordance with JIS K 7121, and is the peak temperature of the main endothermic peak observed with a differential scanning calorimeter (for example, DSC (Differential Scanning Calorimetry) manufactured by Shimadzu Corporation).
[0035] The melt-melt anisotropic aromatic polyester may contain thermoplastic polymers such as polyethylene terephthalate, modified polyethylene terephthalate, polyolefin, polycarbonate, polyamide, polyphenylene sulfide, polyether ether ketone, fluororesin, etc., within the scope of not impairing the effects of the present invention. In addition, the melt-melt anisotropic aromatic polyester may contain various additives such as inorganic substances such as titanium oxide, kaolin, silica, barium oxide, etc., colorants such as carbon black, dyes and pigments, antioxidants, ultraviolet absorbers, light stabilizers, etc.
[0036] (sheath component) The sheath component has a sea-island structure, with the flexible thermoplastic polymer (B polymer) forming the sea component and the molten anisotropic aromatic polyester (C polymer) forming the island component. The flexible thermoplastic polymer (B polymer) forming the sea component may be a polymer having no aromatic ring on the main chain, or a polymer having an aromatic ring on the main chain and having 4 or more atoms on the main chain between the aromatic rings. Specific examples include polyolefins, polyamides, polycarbonates, polyphenylene sulfide (abbreviation: PPS), polyesters such as polyethylene terephthalate, modified polyethylene terephthalate, amorphous polyarylate, and polyethylene naphthalate (abbreviation: PEN), polyether ether ketones, and fluororesins. These flexible thermoplastic polymers may be used alone or in combination of two or more, and one may be the main thermoplastic polymer (e.g., occupying 80% by weight or more) and the other may be added as a thermoplastic polymer. Among these, PPS and PEN are preferably the main thermoplastic polymers. The flexible thermoplastic polymer may also contain various additives such as inorganic substances such as titanium oxide, silica, barium oxide, etc., colorants such as carbon black, dyes or pigments, antioxidants, ultraviolet absorbers, light stabilizers, nucleating agents, etc.
[0037] The melt-melt anisotropic aromatic polyester (C polymer) forming the island component may be the melt-melt anisotropic aromatic polyester described above for the A polymer, and may be the same as or different from the A polymer, but from the viewpoint of affinity, it is preferable that the main structural unit is the same melt-melt anisotropic aromatic polyester. The A polymer and the C polymer may be the same type of polymer with the same main structural unit and, for example, different only in the thermoplastic polymer or additive added.
[0038] Furthermore, the melting point (Mc) of the C polymer can be appropriately selected within a range in which the C polymer can be finely dispersed in the B polymer. For example, the melting point (Mc) of the C polymer may be in the range of (Mb-10) to (Mb+80)°C, or in the range of Mb to (Mb+70)°C, relative to the melting point (Mb) of the B polymer.
[0039] Furthermore, from the viewpoint of spinnability, the melt viscosity η of the C polymer may be, for example, 10 to 60 Pa·s, preferably 20 to 50 Pa·s, and more preferably 25 to 45 Pa·s. The melt viscosity η in the present invention is defined as the melt viscosity at a temperature T (when the melting point (Mc) of the C polymer is 290° C. or higher, T=(Mc+10)° C.; when the melting point Mc is less than 290° C., T=300° C.), a shear rate of 1000 sec -1 The melt viscosity was measured at 100°C.
[0040] (Method of manufacturing core-sheath composite fiber) The core-sheath composite fiber of the present invention can be produced by a production method including at least a kneading step and a discharging step. The production process may further include a heat treatment step.
[0041] In the kneading step, the B polymer and the C polymer used for the sheath component are melted and kneaded using a twin-screw extruder, and the A polymer used for the core component is melted and kneaded using an extruder other than the twin-screw extruder used for the sheath component.
[0042] In particular, in a twin-screw extruder used for kneading the B polymer and the C polymer, the set temperature of the kneading section of the twin-screw extruder is set to (Mb)°C or higher relative to the melting point (Mb) of the B polymer, and to (Mc-20)°C or higher but lower than (Mc)°C relative to the melting point (Mc) of the C polymer, and the rotation of the parallel twin-screw screws rotatably supported in the kneading section makes it possible to finely disperse a plurality of island parts in the sheath component. The extruder for melting and kneading the A polymer used for the core component may be a single screw extruder or a twin screw extruder. When using a raw material in which the B polymer and the C polymer are compounded in advance under the above conditions, the multiple island portions in the sheath component are already finely dispersed, so the extruder for melt-kneading the sheath component may be a single screw extruder or a twin screw extruder.
[0043] In the kneading step, the ratio of the core component to the sheath component may be, for example, 20 / 80 to 97 / 3 as the weight ratio of the core component / sheath component (hereinafter, sometimes simply referred to as the core-sheath ratio) from the viewpoint of improving the resistance to fibrillation and suppressing the exposure of the core component, and may be preferably 50 / 50 to 96 / 4, more preferably 60 / 40 to 95 / 5, even more preferably 70 / 30 to 94 / 6, even more preferably 75 / 25 to 93 / 7, particularly preferably 80 / 20 to 92 / 8, and most preferably 82.5 / 17.5 to 90 / 10. In particular, when the core component is 50% or more, it is preferable because the strength of the composite fiber can be improved. The weight ratio of the core component to the sheath component can be determined, for example, by the weight ratio of the core component and the sheath component respectively charged into each extruder described later during production.
[0044] The ratio of island components in the sheath component may be more than 10% by weight, preferably 15% by weight or more, and more preferably 20% by weight or more. By increasing the ratio of island components, the anchor effect of the island components between the core component and the sheath component can be strengthened. On the other hand, if the ratio of island components is too high, the possibility of the island components agglomerating increases, so the island components may be 40% by weight or less, preferably 35% by weight or less.
[0045] In the extrusion process, the sheath component and the core component kneaded in the kneading process are combined and extruded from a spinneret having a structure shown in FIG. 4, for example, to spin a core-sheath composite fiber having a circular cross section (fiber cross section).
[0046] The die temperature (spinning temperature) during extrusion may be, for example, (Ma+10) to (Ma+60)°C, preferably (Ma+15) to (Ma+40)°C, and more preferably (Ma+20) to (Ma+35)°C, relative to the melting point (Ma) of the A polymer. The shape of the finely dispersed island parts is controlled by the draft value, and the discharged discharged yarn may be drawn at a draft value of 13 to 50, preferably 15 to 45, more preferably 16 to 40, further preferably 19 to 38, and particularly preferably 20 to 35. The discharged yarn means a yarn discharged from a nozzle hole and not stretched, that is, a yarn having a fiber diameter approximately equal to the nozzle hole diameter, and the draft value means the ratio of the take-up speed to the discharge speed during spinning.
[0047] The spun fiber may be further subjected to a heat treatment, which not only increases the oriented crystallinity of the B polymer in the sheath component, but also allows the molten anisotropic aromatic polyester to be solid-phase polymerized, thereby improving the strength of the core-sheath composite fiber.
[0048] In the heat treatment, the spun fiber may be heat-treated under an atmosphere of an inert gas such as nitrogen, or under an atmosphere of an oxygen-containing active gas (eg, air) at normal pressure or reduced pressure. When the heat treatment is performed, the heat treatment atmosphere is preferably a low-humidity atmosphere with a dew point of -50° C. or less, preferably -60° C. or less, more preferably -70° C. or less. The heat treatment conditions include a temperature pattern in which the temperature is gradually increased from (Ma-20)° C. or less, preferably (Ma-30)° C. or less, more preferably (Ma-40)° C. or less, relative to the melting point (Ma) of the A polymer, to the melting point of the sheath component or less. Methods for supplying heat include a method using a gas medium, a method using radiation from a heating plate, an infrared heater, etc., an internal heating method using high frequency waves, etc. The treatment form may be roll-to-roll continuous production, or batch production by reeling or towing the raw spun yarn around a bobbin for heat treatment.
[0049] From the viewpoint of preventing sheath peeling due to adhesion of the yarn after heat treatment, etc., inorganic fine particles may be applied to the surface of the fiber during or after spinning of the fiber and before the heat treatment, if necessary. As the inorganic fine particles, those mainly composed of silicate compounds such as talc and mica are preferable.
[0050] Unlike Patent Document 2, the present invention has good releasability even without adhering inorganic fine particles, but from the viewpoint of further improving the releasability, inorganic fine particles may be adhered. By uniformly attaching inorganic fine particles to the surface of the fiber during or after spinning and before heat treatment, it is possible to prevent the yarns from coming into direct contact with each other and to prevent the yarns from sticking together. Note that most of the inorganic fine particles mainly composed of silicate compounds are inactive, and there is no deterioration in the physical properties of the fiber even when they are attached to the fiber.
[0051] The method of attaching the inorganic fine particles to the surface of the fiber is not limited as long as it can be uniformly attached to the fiber. For example, a method of attaching inorganic fine particles dispersed in a spinning oil solution by stirring using an oiling roller or a glass nozzle is simple and preferable.
[0052] From the viewpoint of uniform deposition on the fiber surface, the inorganic fine particles to be attached to the surface of the sheath-core composite fiber may have an average particle size of, for example, 0.01 to 10 μm, preferably 0.02 to 5 μm. The amount of the inorganic fine particles to be attached to the surface of the sheath-core composite fiber may be in the range of 0.03 to 2.5 mass%, preferably 0.1 to 2.3 mass%.
[0053] (Sheath-core composite fiber) Fig. 1A is a schematic perspective view of a sheath-core composite fiber according to one embodiment of the present invention, and Fig. 1B is a schematic cross-sectional view of the sheath-core composite fiber cut in the longitudinal direction of the fiber. The sheath-core composite fiber 10 has a core portion 12 formed of a core component and a sheath portion 14 formed of a sheath component.
[0054] Fig. 2 is an enlarged cross-sectional view partially enlarging part II in Fig. 1B. As shown in Fig. 1B and Fig. 2, in a cross section (longitudinal cross section) of the sheath-core composite fiber cut in the longitudinal direction of the fiber so as to include the central axis of the fiber, the sheath portion 14 forms a sea-island structure, and a plurality of island portions 18 are formed in the sea portion 16. The island portions are finely dispersed in the sea portion, and the shapes of the island portions are controlled. In the sheath-core composite fiber of the present invention, the ratio of island parts in the sea part is increased while the island parts are finely dispersed. Therefore, the numerous island parts strengthen the anchoring ability of the sheath part to the core part, thereby not only preventing peeling of the sheath part but also preventing fibrillation of the sheath part.
[0055] The islands are basically elliptical and extend in the longitudinal direction of the fiber while being finely dispersed. If the diameter of the island is large, the unevenness of the fiber surface resulting from the island components becomes larger. Since the generation of fibrils is due to the size of the unevenness of the fiber surface, it is preferable that the maximum diameter of the island is small. In addition, it is preferable that the island has a shape that extends long in the longitudinal direction of the fiber, since it can exert an anchoring effect. That is, simply measuring the diameter of the island in one cross section of the fiber does not take into account the contribution of the anchoring effect caused by the length of the island. However, by observing the shape of the island in the longitudinal direction in a micrograph of the sheath and evaluating the shape of the island having the widest width by taking into account not only the width but also the length of the island, it is possible to evaluate the fibrillation while taking into account the contribution of the anchoring effect of the island. To this end, an island having a maximum width W is selected, and then the maximum length L1 of the island is measured, which is the length that overlaps with a diagonal line extending from one end to the other end in the longitudinal direction of the fibers at a predetermined angle α (10°) with respect to the longitudinal direction of the fibers, as shown in FIG. 2, and L1 / W is calculated, which makes it possible to evaluate the shape of the island taking into account the elongation in the longitudinal direction of the fibers.
[0056] First, the island having the maximum width W can be selected from an enlarged image of the fiber longitudinal section. Specifically, the fiber longitudinal section is observed in the fiber longitudinal direction at a distance of 100 μm to 1000 μm using a scanning probe microscope (SPM) described later, and the numerical value of the part where the length of the island in the direction perpendicular to the fiber longitudinal direction (fiber perpendicular direction) is maximum in the observed range is taken as the measured value. However, the observed range does not need to be continuous, and may be the sum of a number of randomly extracted fields of view. For example, in the observed range of the fiber longitudinal section, a number of island parts having a relatively large length in the fiber perpendicular direction are extracted from a large number of island parts extending in the fiber longitudinal direction, and the island part having the maximum width can be determined by comparing the length of the extracted island parts in the fiber perpendicular direction as the island width. In this example, only one of the upper and lower parts of the sheath component (for example, the lower part of FIG. 1B) in the fiber longitudinal section may be taken as the observed range. In this example, the longitudinal cross section of the fiber is observed with a scanning probe microscope to determine the maximum width of the island portion, but any means other than a scanning probe microscope may be used as long as it can determine the maximum width of the island portion. In addition, when cutting the fiber, it is preferable to fix the fiber by embedding it in resin before cutting in order to minimize the effect of stress.
[0057] The maximum width W of the island portion is 0.65 μm or less, preferably 0.60 μm or less, more preferably 0.55 μm or less, and even more preferably 0.50 μm or less. If the maximum width of the island portion exceeds the upper limit, the fibrillation resistance may be insufficient. The maximum width W of the island portion may be 0.07 μm or more, or 0.1 μm or more.
[0058] After selecting an island having a maximum width W, the island is continuously observed in the longitudinal direction, and the maximum length L1 of the oblique length that overlaps with a diagonal line extending from one end of the fiber longitudinal direction to the other end at a predetermined angle α (10°) with respect to the fiber longitudinal direction is measured as shown in FIG. 2. When the ratio L1 / W of the maximum length L1 of the oblique length to the maximum width W is 5.0 or more, the core-sheath composite fiber can improve the anchoring effect of the island while suppressing fibrillation. The L1 / W is preferably 5.1 or more, more preferably 5.2 or more, even more preferably 5.3 or more, and even more preferably 5.5 or more. There is no particular upper limit to the value of L1 / W, but it may be 10 or less.
[0059] The maximum length L1 of the oblique length is a value that varies depending on the value of the maximum width W, and may be, for example, 1.0 μm or more, preferably 1.3 μm or more, more preferably 1.5 μm or more, and even more preferably 1.7 μm or more. When the maximum length L1 of the oblique length is equal to or more than the lower limit, the anchor effect on the core component tends to be enhanced. Moreover, the maximum length L1 of the oblique length may be 3.3 μm or less, preferably 3.1 μm or less, and more preferably 2.9 μm or less. When the maximum length L1 of the oblique length is equal to or less than the upper limit, fibrillation tends to be suppressed.
[0060] In the longitudinal fiber cross section, the length L2 of the island portion having the largest width in the sheath component in the longitudinal fiber direction may be, for example, 450 to 1000 μm, preferably 500 to 800 μm, and more preferably 550 to 650 μm. The longer L2 is, the higher the anchor effect on the core component can be. The longitudinal fiber length of the island portion can be obtained from an enlarged image of the longitudinal fiber cross section. Alternatively, the longitudinal fiber length of the island portion may be obtained using a discharged yarn, and the calculated value may be multiplied by the draft value.
[0061] The thickness of the sheath component may be, for example, 0.8 to 5.0 μm, preferably 0.9 to 4.0 μm, and more preferably 0.9 to 3.8 μm, from the viewpoint of preventing exposure of the core component and ensuring fiber strength.
[0062] As shown in Fig. 3, the thickness of the sheath component can be determined, for example, from an enlarged image of a cross section of a core-sheath composite fiber cut along a plane perpendicular to the longitudinal direction of the fiber (hereinafter sometimes referred to as a "fiber cross section"). Specifically, the fiber cross section is imaged with a scanning microscope or the like, and the radial distances from the outer surface of the core component to the outer surface of the sheath component are measured at any three points that divide the fiber circumference into thirds, and the thickness of the sheath component can be determined from the average value. Note that when cutting the fibers, it is preferable to fix the fibers by embedding them in resin before cutting in order to minimize the effects of stress.
[0063] The single yarn fineness of the core-sheath composite fiber may be, for example, 1 to 120 dtex, preferably 2 to 60 dtex, more preferably 2.5 to 30 dtex, and further preferably 3 to 15 dtex. This single yarn fineness can be measured, for example, in accordance with JIS L 1013 "Testing method for chemical fiber filament yarn." The core-sheath composite fiber may be a monofilament or a multifilament containing two or more monofilaments.
[0064] The sheath-core composite fiber may have a tensile strength in an atmosphere of 25°C of, for example, 10 cN / dtex or more, preferably 13 cN / dtex or more, more preferably 15 cN / dtex or more, even more preferably 18 cN / dtex or more, and even more preferably 20 cN / dtex or more. There is no particular upper limit to the tensile strength, but it may be 30 cN / dtex or less. Here, the tensile strength is a value measured with reference to the JIS L 1013 test method. When the sheath-core composite fiber is a multifilament, taking into account the change in strength due to the alignment of the fibers, one fiber may be taken out of the multifilament and measured as the single yarn tensile strength.
[0065] Sheath-core composite fibers have excellent fibrillation resistance, and when a test fiber is passed through three comb guides arranged alternately at an angle of 120° and a load of 1 g / dtex is applied to each fiber, the fiber is reciprocated 30,000 times at a stroke length of 3 cm and a speed of 95 times / min, and the average number of fluffs (average of 5 times) generated per 3 cm of fiber length may be, for example, 1 or less, and preferably 0.5 or less. Here, fluff can be observed as small fluff (fibril) of 1 mm or less, or fluff or sheath peeling of more than 1 mm, when the sheath-core composite fiber is magnified 20 times with a camera.
[0066] The core-sheath composite fiber of the present invention can be woven or knitted by a conventional method, and can be dyed by a conventional method depending on the type of flexible thermoplastic polymer. For example, when the flexible polymer is a polyester polymer, it can be dyed by a conventional polyester fiber dyeing method using a disperse dye.
[0067] The sheath-core composite fiber of the present invention can be suitably used as various fiber structures, and the fiber structure of the present invention contains at least a part of the sheath-core composite fiber of the present invention. Examples of the fiber structure include one-dimensional structures such as ropes and mixed yarns, and highly processed products such as two-dimensional structures such as woven fabrics, knitted fabrics, and nonwoven fabrics. The fiber structure may be composed of the sheath-core composite fiber alone, or may contain other components within a range that does not impair the effects of the present invention. After the fiber structure is formed, it may be dyed by the above-mentioned dyeing method.
[0068] When the fiber structure is a woven fabric, the weave structure is not particularly limited, and examples thereof include plain weave, twill weave, satin weave, varied plain weave, varied twill weave, varied satin weave, variegated weave, patterned weave, single-layer weave, double weave, multi-layer weave, warp pile weave, weft pile weave, leno weave, etc. When the fiber structure is a knitted fabric, the knit structure is not particularly limited, and examples thereof include circular knit, weft knit, warp knit (including tricot knit and raschel knit), pile knit, plain knit, jersey knit, rib knit, smooth knit (double-sided knit), elastic knit, pearl knit, Denbigh knit, cord weave, atlas weave, chain weave, insertion weave, etc. EXAMPLES
[0069] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following examples and comparative examples, various physical properties were measured by the following methods.
[0070] [Fineness] Based on JIS L 1013:2010 8.3.1 A method, a 100m skein of core-sheath composite fiber was taken using a measuring instrument manufactured by Daiei Scientific Instruments Manufacturing Co., Ltd., and its weight (g) was multiplied by 100 and measured three times per level, and the average of the three measured values was taken as the obtained fineness (dtex).
[0071] [Tensile strength] According to JIS L 1013, a tenacity and elongation tester "TENSORAPID5" manufactured by USTER was used to measure five times for each sample under the conditions of a test length of 20 cm, a tensile speed of 10 cm / min, and an initial load of 0.33 g / dtex, and the average of the five measured values was taken as the strength (cN / dtex). When the core-sheath composite fiber was a multifilament, one fiber was taken out of the multifilament and the single yarn tensile strength was measured.
[0072] [Sheath thickness] The core-sheath composite fiber was embedded in epoxy resin, and the embedded fiber was cut in a plane perpendicular to the longitudinal direction of the fiber to expose the fiber cross section. In this fiber cross section, the radial distance from the outer surface of the core to the outer surface of the sheath was measured using a microscope at three points that divided the fiber circumference into three equal parts, and the average value was calculated to determine the thickness of the sheath component.
[0073] [Island length, maximum island width] The core-sheath composite fiber was embedded in epoxy resin, and the embedded fiber was cut in the fiber longitudinal direction with a cross-section polisher (CP) to expose the fiber longitudinal section. The fiber longitudinal section was observed in the fiber longitudinal direction at 100 μm to 1000 μm with a scanning probe microscope (SPM). Among the numerous islands extending in the fiber longitudinal direction within the observation range, several islands with relatively large lengths in the fiber perpendicular direction were extracted, and the lengths of the extracted islands in the fiber perpendicular direction were compared as island widths, and the maximum island width W of the island with the largest width was determined. In addition, the length L2 in the fiber longitudinal direction of the island with the maximum width W was measured.
[0074] [Maximum island diagonal length] Next, for the island portion having the maximum width W, the longest line segment among the lengths overlapping with an oblique line extending from one end to the other end in the longitudinal direction of the fibers at a predetermined angle α (10°) with respect to the longitudinal direction of the fibers was measured as the maximum oblique length L1 of the island portion.
[0075] [Wear resistance] Using a TM-type clinging force tester (model TM-200) manufactured by Daiei Kagaku Seiki Seisakusho, the fibers to be tested were passed through three comb guides arranged alternately at an angle of 120°, a load of 1 g / dtex was applied to each fiber, and 30,000 reciprocating motions were given at a stroke length of 3 cm and a speed of 95 times / min, and the state of fluff was confirmed by magnifying it 20 times with a camera. The above test was carried out five times, and the presence or absence of fluff was observed for each 3 cm length of the fiber. The generated fluff was distinguished between minute fluff of 1 mm or less and fluff of more than 1 mm in length, and was evaluated according to the following criteria. (Whether or not fluff occurs) ◎: No fluff was observed in any of the five tests ○: Fuzz was observed once or more out of five tests, but no fuzz longer than 1 mm was observed ×: Fluff was observed once or more out of five tests, and fluff longer than 1 mm was observed once or more. Furthermore, for samples in which fluff was observed at least once out of five tests, the number of fluff particles that occurred was counted and calculated as the average value for the five tests.
[0076] [Example 1] Core-sheath composite fibers were produced according to the following method. For the core component, a melt-anisotropic aromatic polyester with a molar ratio of (P:HBA) and (Q:HNA) of 73 / 27 [melting point (Ma): 278°C, melt viscosity (MVa): 32.1 Pa s] was used as polymer A. For the sheath component, PEN [melting point (Mb): 266.3°C, melt viscosity (MVb): 100 Pa s] was used as polymer B forming the sea component, and the same melt-anisotropic aromatic polyester as polymer A above [melting point (Mc): 278°C, melt viscosity (MVc): 32.1 Pa s] was used as polymer C forming the island component.
[0077] In the kneading process, the core component and the sheath component were melt-kneaded in separate extruders. In the kneading process for the sheath component, the B polymer and the C polymer were mixed so that the ratio of the island component in the sheath component was 30% by weight, and after the start of kneading and extrusion, the set temperature of the kneading section of the twin-screw extruder was set to 266°C ((Mc-12)°C) to knead thoroughly (low-temperature kneading process). In the discharge process, the core-sheath composite fiber was spun at a spinning temperature of 310°C and a draft value of 22.3 times from a spinneret having the structure shown in Figure 4, which was controlled so that the sheath component ratio was 0.35 (core-sheath ratio (weight ratio) 65 / 35), to obtain a monofilament core-sheath composite fiber of 10.3 dtex. The spinnability was good, and it was possible to collect the fiber without any breakage.
[0078] Next, in the heat treatment step, the obtained fiber was rewound onto a heat treatment bobbin, and the treatment temperature was gradually increased to a maximum temperature of 260° C. and was performed for 18 hours in a nitrogen gas atmosphere. There was no problem with the unwinding property from the heat treatment bobbin, and the obtained heat-treated yarn had the properties shown in Table 5.
[0079] [Examples 2 to 8] Core-sheath composite fibers were produced in the same manner as in Example 1, except that the core-sheath ratio, the ratio of island components in the sheath component, the number of filaments, the single yarn fineness, and the draft value were changed as shown in Table 5. The results are shown in Table 5. In all cases, the spinnability was good, and the fibers could be harvested without any yarn breakage.
[0080] [Comparative Example 1] A chip blend of B polymer and C polymer chips, which are the sheath component, was used, and the B polymer and C polymer were mixed so that the ratio of island components in the sheath component was 30% by weight. The mixture was melt-kneaded at 310°C using a single-screw extruder in a low-temperature kneading process, and spun at a spinning temperature of 310°C and a draft value of 9.9 times using a spinneret having the structure shown in FIG. 4, which was controlled so that the sheath component ratio was 0.35 (core-sheath ratio (weight ratio) was 65 / 35). Spinning and heat treatment were carried out in the same manner as in Example 1 to produce a core-sheath composite fiber. The spinnability was poor, and there were cases where the yarn was broken. The results are shown in Table 5.
[0081] [Comparative Example 2] A core-sheath composite fiber was produced in the same manner as in Comparative Example 1, except that the ratio of island components in the sheath component was 20% by weight. The spinnability was poor, and there were cases of yarn breakage. The results are shown in Table 5.
[0082] [Comparative Example 3] A core-sheath composite fiber was produced by spinning and heat treatment in the same manner as in Comparative Example 1, except that the ratio of island components in the sheath component was mixed to be 5% by weight. As described in Patent Document 1, since the ratio of island components in the sheath component was 10% by weight or less, the spinnability was good and it was possible to collect the fiber without breaking the yarn. The results are shown in Table 5.
[0083] [Comparative Example 4] A core-sheath composite fiber was produced in the same manner as in Comparative Example 1, except that the sheath component ratio was 0.15 (core-sheath ratio (weight ratio) was 85 / 15) and spinning was performed at a draft value of 15.5. The spinnability was poor, and there were cases of yarn breakage. The results are shown in Table 5.
[0084] [Comparative Example 5] A core-sheath composite fiber was produced by spinning and heat treatment in the same manner as in Comparative Example 1, except that in the kneading step of the sheath component, a low-temperature kneading step was carried out in the same manner as in Example 1. The spinnability was good, and it was possible to collect the fiber without any breakage. The results are shown in Table 5.
[0085] [Table 5]
[0086] As shown in Table 5, in all of Examples 1 to 8, even when the proportion of the melt-type anisotropic aromatic polyester in the sheath component was increased, high abrasion resistance and spinnability could be achieved by controlling the shape of the islands in the sea-island structure of the sheath component.
[0087] In all of Examples 1 to 8, no fuzz larger than 1 mm was observed in the abrasion test with 30,000 reciprocating motions, and no sheath peeling occurred, showing excellent abrasion resistance. In particular, in Examples 2 and 3, even minute fibrils of 1 mm or less were not observed, possibly because the maximum width of the island was small. Furthermore, in Examples 1 and 4 to 5, although the maximum width of the island was larger than in Examples 2 and 3, even minute fibrils of 1 mm or less were not observed, or were observed only once out of five measurements, possibly because the maximum length L1 of the diagonal length of the island / maximum width W can be increased by making the island width smaller and the island length longer.
[0088] In particular, in Examples 4 and 5, the shape of the islands in the sheath component was controlled to maintain wear resistance even when the sheath was made thin, and the strength was also high due to the high core component ratio.
[0089] Moreover, even in Example 6, which has a small single yarn fineness, and Examples 7 to 8, which have a large single yarn fineness, better abrasion resistance is shown than in Comparative Examples 1 to 3 by controlling the island shape in the sheath component.
[0090] On the other hand, in Comparative Example 1, since the specific melt-kneading step was not performed on the sheath component, the spinnability was poor and yarn breakage occurred during spinning. In addition, in Comparative Example 1, the core-sheath ratio and the ratio of island components in the sheath component were similar to those in Example 1, but the maximum width of the island components in the sheath of the obtained core-sheath composite fiber was larger than that in Example 1, indicating that the sheath had large islands. Furthermore, perhaps because the maximum length / maximum width of the diagonal length of the island components was small, the anchor effect of the sheath component could not be exerted, and when evaluating the fluff in the abrasion resistance test, not only were small fluff (fibrils) of 1 mm or less generated, but the number of fluffs generated was greater than in Example 1, and fluff larger than 1 mm and sheath peeling also occurred. In addition, the fiber strength also showed a value lower than that of Example 1.
[0091] Comparative Example 2 has the same core-sheath ratio and island component ratio in the sheath component as Example 2, but since the sheath component is not subjected to a specific melt-kneading process, the maximum width of the island portion is larger than that of Example 2, indicating that the island portion is larger. In the evaluation of fluff in the abrasion resistance test, the number of fluffs generated is greater than that of Example 2, and fluff larger than 1 mm and sheath peeling also occurred. In addition, the fiber strength is lower than that of Example 2.
[0092] In Comparative Example 3, although the proportion of the melt-anisotropic aromatic polyester in the sheath component is lower than in Examples 1 and 2, the maximum island width is larger than in Examples 1 and 2, indicating that the island has a large island. In the evaluation of fluff in the abrasion resistance test, the number of fluffs generated is greater than in Examples 1 and 2, and fluff larger than 1 mm and sheath peeling occurred. In addition, the fiber strength is lower than in Examples 1 and 2.
[0093] Comparative Example 4 has the same core-sheath ratio and the ratio of island components in the sheath component as Example 5, but since the specific melt-kneading process is not performed on the sheath component, the maximum length / maximum width of the diagonal length of the island part is small, and fluff and sheath peeling larger than 1 mm occur.
[0094] In Comparative Example 5, the core-sheath ratio and the ratio of island components in the sheath component were similar to those in Example 1. Since the sheath components were subjected to a specific melt-kneading process, the maximum width of the island components was small. However, since the draft value during spinning was small, the maximum length / maximum width of the island parts in the diagonal length was small, and fluff and sheath peeling larger than 1 mm occurred. [Industrial Applicability]
[0095] The sheath-core composite fiber of the present invention can suppress fibrillation while maintaining high strength and high elastic modulus by increasing the proportion of molten anisotropic aromatic polyester in the sheath component, and therefore can be used in advanced processed products such as tension members (electric wires, optical fibers, umbilical cables, heater wire core threads, cords for various electrical products such as earphone cords, etc.), sail cloth, ropes (marine, mountain climbing, cranes, yachts, tugs, etc.), ropes, land nets, slings, lifelines, fishing lines, sewing threads, screen cords, fishing nets, longlines, geogrids, protective gloves, ripstop protective clothing and outdoor clothing, rider suits, sports rackets, guts, reinforcing materials for medical catheters, suture threads, screen gauze, filters, base fabrics for printed circuit boards, mesh conveyor belts, papermaking belts, dryer canvases, airships, balloons, airbags, speaker cones, reinforcing materials for various hoses and pipes, and reinforcing materials for rubber and plastic materials such as tires and conveyor belts. In addition, because it can be dyed using standard methods, it is particularly well suited for use in sail cloth, ropes, land nets, fishing lines, fishing nets, longlines, ripstop protective clothing and outdoor clothing, reinforcing materials for rubber and plastics, and advanced processed products such as general clothing.
[0096] Although the preferred embodiment of the present invention has been described above with reference to the drawings, a person skilled in the art will easily imagine various changes and modifications within the obvious scope upon reading the specification. Therefore, such changes and modifications are interpreted as falling within the scope of the invention as defined by the claims.
Claims
1. A core-sheath composite fiber having a sea-island structure in which a core component contains a melt-type anisotropic aromatic polyester (A polymer), a sheath component contains a flexible thermoplastic polymer (B polymer) and a melt-type anisotropic aromatic polyester (C polymer), the B polymer forms a sea component, the C polymer forms island components, and a plurality of island portions made of the island components are dispersed in a sea portion made of the sea component, The ratio of the island component in the sheath component is more than 10% by weight, and In a cross section of the sheath-core composite fiber cut in the longitudinal direction of the fiber, the maximum width W of the island portion is 0.65 μm or less, a sheath-core composite fiber, wherein, in an island portion having the maximum width W, among the island portions that are in contact with an oblique line in the sheath component extending at a predetermined angle of 10° with respect to the longitudinal direction of the fiber from one end to the other end in the longitudinal direction of the fiber, a ratio L1 / W of a maximum length L1 of a diagonal length that overlaps with the oblique line to a maximum width W of the island portion is 5.0 or more.
2. 2. The sheath-core composite fiber according to claim 1, wherein the maximum length L1 of the oblique length is 1.0 μm or more.
3. 3. The sheath-core composite fiber according to claim 1 or 2, wherein in a cross section of the sheath-core composite fiber cut in the fiber longitudinal direction, the length L2 of the island portion in the sheath component in the fiber longitudinal direction is 450 to 1000 μm.
4. 4. The sheath-core composite fiber according to claim 1, wherein the thickness of the sheath component is 0.8 to 5.0 μm.
5. 5. The sheath-core composite fiber according to claim 1, wherein the A polymer and the C polymer are composed of the same melt-dispersible anisotropic aromatic polyester as main structural units.
6. 6. The core-sheath composite fiber according to claim 1, wherein the weight ratio of the core component to the sheath component, that is, core component / sheath component, is 20 / 80 to 97 / 3.
7. 7. The sheath-core composite fiber according to claim 1, wherein the single fiber fineness of the sheath-core composite fiber is 1 to 120 dtex.
8. A method for producing a core-sheath composite fiber having a sea-island structure in which a core component contains a melt-type anisotropic aromatic polyester (A polymer), a sheath component contains a flexible thermoplastic polymer (B polymer) and a melt-type anisotropic aromatic polyester (C polymer), the B polymer forms a sea component, the C polymer forms island components, and a plurality of island components made of the island components are dispersed in a sea part made of the sea component, the method comprising the steps of: a kneading step in which the B polymer and the C polymer used for the sheath component are kneaded using a twin-screw extruder at a temperature of (Mb)°C or higher relative to the melting point (Mb) of the B polymer and at a temperature of (Mc-20)°C or higher but lower than (Mc)°C relative to the melting point (Mc)°C of the C polymer, and the A polymer used for the core component is melted and kneaded using an extruder different from the twin-screw extruder used for the sheath component; and a discharge step in which the sheath component and the core component respectively kneaded in the kneading step are combined and discharged to obtain a discharged yarn. A step of taking up the discharged discharged yarn at a draft value of 13 to 50, which is the ratio of the winding speed to the discharge speed; A method for producing a core-sheath composite fiber comprising at least the steps of:
9. 9. The method for producing the sheath-core composite fiber according to claim 8, further comprising a heat treatment step of subjecting the fiber obtained in the discharge step to a heat treatment.
10. A fiber structure comprising at least a part of the core-sheath composite fiber according to any one of claims 1 to 7.
Citation Information
Patent Citations
Production of thermotropic liquid crystal polymer filament
JP1995126916A
Sheath-core type conjugate fiber
JP1999081031A
Conjugate fiber and its woven fabric
JP2002020932A
Core-sheath conjugate fiber
JP2005133250A
Core-sheath conjugate fiber
JP2007126760A